Hubungan Struktur Sistem Pengendalian Manajemen dan Proses Sistem Pengendalian Manajemen dengan Kinerja Keuangan Perusahaan pada PT. Kereta Api Indonesia (Persero) - Imas Purnamasari (STIE Pelita Nusantara Semarang, 2009)
Reaching more than 100%, the decrease of financial performance of PT.KAI in 2006 is the highest in recent years. This condition is, to certain extent, caused by insufficient control system. The structure and process of management control system are two parts researchable in an effort to explain the financial performance of PT. KAI. This research is, therefore, conducted to identify: (1) the simultaneous correlation between the structure and process of managementcontrol system and company financial performance, (2) the correlation between the structure of management control system and company financial performance, and (3) the correlation between the process of management control system and company financial performance.This research uses survey-explanatory method by using three different levels ofmanagement as research respondent, namely top, middle, and low. Each level represents financial performance and operation area in terms of return on investment (ROI) year 2006.Findings of the research are as follows: (1) the structure and process of management control system have a simultaneously positive correlation with financial performance. This means that the company financial performance is strongly determined by the system of management control consisting of structure and process, (2) individually, the structure of management control system has positive correlation with financial performance, and (3) theprocess of management control system has positive correlation with financial performance.